PENGARUH KUALITAS LAYANAN TERHADAP LOYALITAS MELALUI KEPUASAN KONSUMEN PENGGUNA JASA TRANSPORTASI UDARA RUTE PALANGKA RAYA - JAKARTA - Meitiana, Meitiana (IQTISHODUNA, 2014)
The increase in number of airlaines industry in Indonesia has caused price competition betweenairlines company, especially for the Palangka Raya - Jakarta route. In order to survive in this industry, theairlines company has made efficiency toreduce the costs. As thr result, service quality became lower, and it willaffecting consumer satisfaction. The objectives of this research are to analyze the effect of service qualitytowards loyalty through consumer satisfaction. This study used quantitative research method, the datacollection used questionnaires and scoring technique used Likert scale. The sample was 100 respondents.This correlation study aims to measure the effects of a particular variable towards other variables. The dataprocessing was analyzed by using Structure Equation Modeling (SEM) with Partial Least Square (PLS) software.The test results of the three hypotheses with PLS software indicated that the two hypotheses were acceptedand the one hypotheses were rejected. Service quality had significant effect towards consumers satisfaction.While consumers satisfaction had not insignificant effect towards loyalty. Then service quality had significanteffect toward loyalty.